Racial disparity in all‐cause mortality among hepatitis C virus‐infected individuals in a general US population, NHANES III. Issue 5 (1st December 2016) - Emmanuel, B.; Shardell, M. D.; Tracy, L.; Kottilil, S.; El‐Kamary, S. S.
Summary: There are few long‐term nationally representative studies of all‐cause mortality among those infected with hepatitis C virus (HCV). When an additional 5 years of data were made publicly available in 2015, the Third National Health and Nutrition Examination Survey Linked Mortality File became the longest nationally representative study in the United States. Our objective was to update the estimated HCV‐associated all‐cause mortality in the general US population and determine any differences by sex, age and race/ethnicity. HCV status was assessed in 9117 nationally representative adults aged 18‐59 years from 1988 to 1994, and mortality follow‐up of the same individuals was completed through 2011 and made publicly available in 2015. There were 930 deaths over a median follow‐up of 19.8 years. After adjusting for all covariate risk factors, chronic HCV had 2.63 times (95% CI: 1.59‐4.37; P= .0002) higher all‐cause mortality rate ratio (MRR) compared with being HCV negative. All‐cause MRR was stratified by sex, age and race/ethnicity. Only race/ethnicity was a significant effect modifier of MRR ( P <.0001) as the highest MRR of chronic HCV compared to HCV negative was 7.48 (95% CI: 2.15‐26.10, P =.001) among Mexican Americans, 2.67 (95% CI: 2.67‐5.56, P =.009) among non‐Hispanic Whites and 2.02 (95% CI: 1.20‐3.40, P =.007) among non‐Hispanic Blacks. Racial disparity was seen in the all‐cause mortality as Mexican Americans with chronic HCV had approximately seven times higher mortality rate than HCV‐negative individuals. This suggests that these at‐risk individuals should be targeted for HCV screening and treatment, given the availability of new highly effective HCV therapies.